Kepentingan Indonesia Memberikan Beasiswa Seni dan Budaya Indonesia (BSBI) Bagi Warga Negara Asing Tahun 2018-2021 - Arismawati, Indaka Nurita; Hartati, Anna Yulia (Kajian Hubungan Internasional, 2024)
The Indonesian Arts and Culture Scholarship (BSBI) or more popularly known as the Indonesian Art and Culture Scholarship (IACS) is one of the Indonesian government's efforts to carry out public diplomacy with the international community in the field of arts and culture. The purpose of this research is to find out what interests Indonesia has in providing Indonesian Arts and Culture Scholarships (BSBI) for foreign citizens. The BSBI program can be used as an effort by the Indonesian government to protect these things as well as as a means to maintain the quality of the positive image of the Indonesian nation. This research uses qualitative research methods, data samples were obtained from previous research, the official website of the Ministry of Foreign Affairs, diplomacy websites, news, journals and newsletters. From the results of the analysis, it was found that the Indonesian Arts and Culture Scholarship (BSBI) could be used as a tool to promote the interests of Indonesia's image in terms of environmental quality, both in terms of geography, materials and the quality of Indonesian society. Efforts to maintain national protection which can be realized by establishing relations with friendly countries. Boosting the Indonesian economy to invite investors, increasing international trade so that GDP can increase every year. Apart from that, the Indonesian Arts and Culture Scholarship (BSBI) is also an effort to protect culture which is targeted at Indonesian youth as the next generation as well as BSBI participants as a reinforcement of culture maintenance as a form of facility established by Indonesia in the international scope.Keywords: Public Diplomacy, Indonesian Interests, ImageABSTRAKBeasiswa Seni dan Budaya Indonesia (BSBI) atau lebih populer disebut dengan istilah Indonesia Art and Culture Scholarship (IACS) adalah salah satu upaya pemerintah Indonesia untuk melakukan diplomasi publik dengan masyarakat internasional dalam bisang seni dan budaya. Tujuan dari penelitian ini adalah untuk mengetahui apa kepentingan Indonesia memberikan Beasiswa Seni dan Budaya Indonesia (BSBI) bagi warga negara asing. Program BSBI bisa dijadikan sebagai upaya pemerintah Indonesia untuk melindungi hal-hal tersebut selain itu juga sebagai sarana untuk mempertahankan kualitas citra positif bangsa Indonesia. Penelitian ini menggunkan metode penelitian kualitatif , pengambilan sample data diperoleh dari penelitian terdahulu, website resmi Kemlu, website diplomasi, berita, jurnal,dan berita. Dari hasil analisis yang didapat bahwa Beasiswa Seni dan Budaya Indonesia (BSBI) bisa di jadikan sebagai alat untuk mempromosikan kepentingan citra Indonesia dalam kualitas lingkungan baik dilihat dari segi geografis, material, serta kualitas masyarakat Indonesia. Upaya untuk mempertahankan perlindungan nasional yang bisa terwujud karena menjalin hubungan dengan negara sahabat. Mendongkrak ekonomi Indonesia untuk mengundang para investor , meningkatkan perdagangan internasional sehingga GDP setiap tahun bisa meningkat. Selain itu Beasiswa Seni dan Budaya Indonesia (BSBI) juga sebagai upaya perlindungan kultur yang mana disini di targetkan untuk pemuda Indonesia sebagai generasi penerus serta peserta BSBI sebagai penguat culture maintenance sebagai bentuk fasilitas yang dibentuk oleh Indonesia dalam lingkup internasional.